CAN WE USE NEUROTROPHINS FOR CAROTID PLAQUE VULNERABILITY ASSESSMENT – IVUS VH CASE SERIES. (June 2022) - Yaneva-Sirakova, Teodora; Traykov, Latchezar; Zlatancheva, Galina; Karamfiloff, Kiril; Hristova, Julieta; Vassilev, Dobrin
Abstract : Objective: Defining carotid atherosclerotic plaque vulnerability is problematic. The combination between imaging and biomarkers may be of practical significance for future assessment of extracranial stenoses. Brain derived neurotrophic factor (BDNF) and neuronal growth factor (NGF) are neurotrophins. There are some studies, which suggest association between endothelial dysfunction and circulating BDNF, impaired neurotrophins' endothelial secretion in atherosclerosis and correlation between BDNF concentration and Agatson's score, as well as coronary plaque vulnerability. Neurotrophins also play important role in cerebral functioning. Their role in carotid atherosclerosis is not known. Design and method: We share the results of 13 patients with angiographically significant carotid stenoses. The plaque morphology was assessed with IVUS VH and we evaluated their serum BDNF and NGF concertation. All the patients were without coronary artery disease or fully revascularized, as well as without significant or symptomatic peripheral artery disease. We had the results for BDNF and NGF from a reference group without any atherosclerotic disease. SPSS (IBM) was used for the statistical analysis, p < 0.05, CI 95%. Results: The patients with significant carotid stenoses had lower mean BDNF values than the reference group. There was correlation between luminal diameter and BDNF (p = 0.049; r = -0.605), total Ca2+ area (mm2) and BDNF (r = 0.681, p = 0.021), Proximal Ca2+area and BDNF (p = 0.007, r = 0.784), Necrotic core % in the proximal plaque area and NGF (r = 0.891, p = 0.001) Conclusions: BDNF concentration was negatively correlated with the maximal values for minimal luminal diameter and positively with total Ca2+ plaque area, t.i. with plaque stability. We found positive correlation with necrotic core % and NGF values. This case series is small, and a much larger sample is needed to define precisely any association. Nevertheless, this is a beginning of the study for the potential role of neurotrophins in carotid plaque morphology, either by their local endothelial secretion or by modification of their central secretion from the altered cerebral hemodynamics. They may be both markers and factors for carotid plaque vulnerability. The work was partially funded by a Research GRANT 2020 number 133 from Medical University Sofia, Bulgaria.